Analysis of the Service Quality of Outpatient Registration at the Hospital Based on the Level of Patient Satisfaction - Nabilatul Fanny; Supawan Masthong; Nikmatu Zulia; Muhammad Alfi Laksana Putra (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Health services are a collection of various types of health services, ranging from health promotion, disease prevention, disease healing, health rehabilitation as organ transplantation. Quality health service is a health service that is needed, in this case it will be determined by the health care profession, and at the same time desired by the patient/consumer or the community and affordable by the people's purchasing power. The quality of hospital services can be seen from the aspect that influences it. The four aspects are climatic aspects, efficiency and effectiveness aspects, patient safety aspects, and patient satisfaction aspects. The type of research used for this research is descriptive quantitative. The population in this study were all outpatients at the Assalam Gemolong General Hospital, with a total sample of 100 respondents. The sampling technique used a purposive sampling approach. The data collection techniques used are observation, interviews, and questionnaires. Meanwhile, data analysis was carried out using Univariate analysis (descriptive analysis) aimed at explaining or describing the characteristics of each research variable. Based on the results of univariate analysis, it can be seen that the level of patient satisfaction at the outpatient registration service is in the Very Satisfied category as many as 30 respondents (30%), Satisfied 58 respondents (58%), Unsatisfied as many as 11 respondents (11%), and Not Satisfied Satisfied as many as 3 respondents (3%). Many things are felt by patients about comfort at the Assalam Gemolong general hospital, the relationship between patients and officers is also felt very good, technical competence of officers is good, and in terms of cost, patients also feel that it is very affordable. The conclusion from these results shows that the quality of the outpatient registration service at the Assalam Gemolong General Hospital is good, this is based on a good level of patient satisfaction.